The Development of Matching Card Book in Improving Students’ Vocabulary Mastery - Febrianti, Nissa; Shofiyuddin, Muh (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2025)
Vocabulary is a crucial element in mastering English language; however, many students struggle to learn it due to ineffective learning methods and lack of interesting media. This study aims to create an engaging Matching Card Book as an interactive print-based learning resource aimed at improving vocabulary mastery among seventh-grade students. This research employs the Research and Development (R&D) method, utilizing the ADDIE model, which encompasses the stages of Analysis, Design, Development, Implementation, and Evaluation. This media has received validation from both material and media experts with the result of “very feasible” both in terms of content and design. To test the effectiveness of the media quasi-experimental design was employed that included a non-equivalent control group. The findings showed that the Matching Card Book significantly improved students’ vocabulary scores with the experimental group (average post-test 87.31) outperforming the control group (average post-test 75.31). The implication of this study suggests that interactive and visually engaging media can bridge the gap in vocabulary learning and serve as an effective alternative especially in educational environments that have limited technological resources. The Matching Card Book is proven to be an interesting, easy to use, and effective media in improving students' vocabulary mastery and promote more active student participation in English learning.